1997
DOI: 10.1021/bi9717688
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate May Be Required for Ligation of Manganese in the Oxygen-Evolving Complex of Photosystem II

Abstract: It was previously shown in the photosystem II membrane preparation DT-20 that photoxidation of the oxygen-evolving manganese cluster was blocked by 0.1 mM formate, unless 0.2 mM bicarbonate was present as well [Wincencjusz, H., Allakhverdiev, S. I., Klimov, V. V., and Van Gorkom, H. J. (1996) Biochim. Biophys. Acta 1273, 1-3]. Here it is shown by measurements of EPR signal II that oxidation of the secondary electron donor, YZ, is not inhibited. However, the reduction of is greatly slowed and occurs largely by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 18 publications
3
40
0
2
Order By: Relevance
“…Importantly, they found that bicarbonate increases the binding affinity and photooxidation rate of the first two Mn II ions, implicating a high affinity pair of Mn II ions involved in bicarbonate-dependent electron transfer from Mn II (27). They also found definitive evidence for bicarbonate enhancing the rate of light-induced charge separation within the intact holo-WOC-PSII at a site on the donor side of PSII, as well as for stabilizing the holo-WOC-PSII against thermal deactivation (27)(28)(29). We speculate that this greater thermal stability could have provided an evolutionary advantage to PSII precursors in the Archean period when ambient temperatures are predicted to have been substantially greater than today (1).…”
Section: Was There a Transitional Electron Donor Before Water?mentioning
confidence: 94%
“…Importantly, they found that bicarbonate increases the binding affinity and photooxidation rate of the first two Mn II ions, implicating a high affinity pair of Mn II ions involved in bicarbonate-dependent electron transfer from Mn II (27). They also found definitive evidence for bicarbonate enhancing the rate of light-induced charge separation within the intact holo-WOC-PSII at a site on the donor side of PSII, as well as for stabilizing the holo-WOC-PSII against thermal deactivation (27)(28)(29). We speculate that this greater thermal stability could have provided an evolutionary advantage to PSII precursors in the Archean period when ambient temperatures are predicted to have been substantially greater than today (1).…”
Section: Was There a Transitional Electron Donor Before Water?mentioning
confidence: 94%
“…Hydrogencarbonate (bicarbonate), which is important during the photo-assembly of the Mn 4 O x Ca cluster, 58 was recently proven not to be a tightly bound constituent of the functional complex.…”
mentioning
confidence: 99%
“…There is an evidence that PS II-associated CA generates bicarbonate ions at a rate sufficient to bound protons released in the inner space of thylakoid in the process of photosynthetic oxidation of water [9]. Hence, CA prevents acidic denaturation of manganese cluster of PS II, as critical increase in local H + concentration may damage the active centers of the complex and result in their destruction with manganese release in liquid environment [10,11].…”
mentioning
confidence: 99%